PENINGKATAN SIFAT TANAH LIAT DENGAN KALSIT DAN SILICA FUME: KUAT TEKAN BEBAS - Dian Adiputra Purba; Syahril; Sandy D Sagala (LPPM Universitas Negeri Jakarta, 2025)
This study investigates the enhancement of clay soil properties by adding calcite and silica fume to address challenges such as low bearing capacity and high compressibility. A total of 51 soil samples were prepared, with 3 samples for each variant, treated with 5% calcite and varying silica fume concentrations (6%, 8%, 10%, 12%). The samples were cured for 0, 3, 7, and 14 days. Unconfined compressive strength (UCS) tests were conducted to evaluate the mechanical properties. Results revealed significant improvements, with UCS increasing from 0.412 kg/cm² in untreated soil to 1.724 kg/cm² in samples treated with 5% calcite and 12% silica fume after 14 days of curing. These values meet or exceed typical strength requirements for construction purposes, reinforcing the effectiveness of calcite and silica fume as stabilizing agents. The enhancement is attributed to the pozzolanic reaction between the additives and the soil, forming calcium silicate hydrate (CSH) and strengthening the soil's microstructure. The findings indicate that calcite and silica fume effectively improve soil stability, offering a promising solution for geotechnical applications. Future research should focus on evaluating the long-term stability of treated soils under various environmental conditions and exploring additional curing methods to optimize the chemical reactions further.